Multigenerational metabolic disruption: Developmental origins and mechanisms of propagation across generations - Davis, Daniel D.; Diaz-Castillo, Carlos; Chamorro-Garcia, Raquel (Frontiers in Toxicology, 2022)
It has been long known that the environment plays a critical role in the etiology of disease. However, it is still unclear how the large variety of environmental factors humans are exposed to interact with each other to lead to disease. Metabolic disorders are just one example of human disorders that have been associated with environmental exposures. Obesity and type 2 diabetes have become a health and economic burden worldwide as the number of affected people has tripled in the last 40 years. Animal and human studies have shown a strong association between exposure to environmental chemicals during critical windows of susceptibility such as periconception, prenatal, and early life, whose effect can persist through development and across generations. However, little is known about the mechanisms driving this persistence. Here, we review historical and current knowledge on the effect of exposure to environmental factors during in utero development and discuss mechanisms for these disorders to be propagated across generations.